The influence of a low-molecular (below 5 kD) fraction from newborn piglet hearts on biochemical parameters of rat blood serum after myocardial infarction - Gulevsky, O. K.; Abakumova, O. S.; Moiseyeva, N. M.; Gorina, O. L.; Moiseyev, А. I. (Reports of the National Academy of Sciences of Ukraine, 2016)
The influence of a low-molecular fraction (below 5 kD) isolated from newborn piglet hearts by the method of ultrafiltration on the cardiac muscle regeneration in rats with the model of catecholamine myocardial infarction in comparison with the reference drug Actovegin is investigated. Chromatographic and biochemical studies show that the compositions of low-molecular substances from the fraction and reference preparation Actovegin differ quantitatively and qualitatively. In in vivo studies, the significant differences in the effectivenesses of the action of drug Actovegin and the low-molecular fraction on the regenerative processes in myocardium after experimental infarction are revealed. In particular, it is established that the administration of the fraction below 5 kD to experimental animals causes a decrease and a normalization in the activity of marker enzymes of myocardial infarction in comparison with the control (saline) and preparation Actovegin.